Social representations of anorexia among university students and risk factors: possible relations - Polli, Gislei Mocelin; da Silva, Jenifer Cristina Clementino; Pereira, Marilisa Graner; dos Reis, Ramiliane Aparecida; Peruci, Tamy Talita; Gelinski, Eliana Motter Müller; Gebara, Telma Souza e Silva (Psico, 2018)
Anorexia is a serious disease, characterized by a distorted body image that leads to extreme behavior. It mainly affects young women. This study sought to identify the social representations of anorexia and the presence of risk factors for its development among female students from different university courses. It sought to establish relationships between anorexia risk factors, body mass index, study area, body satisfaction and social representations. A questionnaire composed by the EAT-26, scale of body silhouettes and open questions about what students knew about anorexia was applied. The data were subjected to statistical and lexicographic analysis. 29% of the students presented risk factors for anorexia. Increased BMI and body dissatisfaction are related to the presence of risk factors. Social representations of anorexia demonstrate the characterization of the disease, very close to scientific knowledge. ***Representações sociais da anorexia entre estudantes universitárias e fatores de risco: possíveis relações*** A anorexia é uma doença grave, caracterizada por uma imagem corporal distorcida que leva a comportamentos extremos. Acomete principalmente jovens mulheres. Este estudo procurou identificar as representações sociais da anorexia e a presença de fator de risco para seu desenvolvimento entre 100 estudantes do sexo feminino de diferentes cursos superiores. Buscou estabelecer relações e entre fator de risco para anorexia, índice de massa corporal, curso superior e satisfação corporal e representações sociais. Foi aplicado um questionário composto pelo EAT-26, escala de silhuetas corporais e questões abertas sobre o que as estudantes sabiam sobre a anorexia. Os dados foram alvo de análises estatísticas e lexicográficas. 29% das estudantes apresentaram fator de risco para anorexia. IMC aumentado e insatisfação corporal estão relacionados à presença de fator de risco. As representações sociais da anorexia demonstram a caracterização da doença, muito próxima do conhecimento científico.